Validation of the Driver Behaviour Questionnaire in a representative sample of drivers in Australia. (January 2016) - Stephens, A.N.; Fitzharris, M.
Highlights: The 28-item four-factor Driver Behaviour Questionnaire was confirmed on a large sample of drivers in Australia. Multigroup confirmatory factor analysis (MGCFA) showed that the DBQ was equivalent across gender. MGCFA showed that the DBQ was also equivalent across drivers aged 24–64 years. Equivalence could not be supported for the youngest (17–25) or oldest (65+) drivers. The four-factor 28-item DBQ did not fit fleet drivers, suggesting a fleet specific DBQ might be required. Abstract: The Driver Behaviour Questionnaire (DBQ) is a widely used measure of driving behaviours that may increase a driver's risk of crash involvement. However, there are several different versions of the DBQ varying in terms of number of items and factor structure. The aim of the current research was to assess the construct validity of the popular 28-item four-factor DBQ solution in a representative sample of drivers in Australia. A further aim was to test the factorial invariance of the measure across gender, age and also between fleet and non-fleet drivers using multigroup confirmatory factor analyses. Data on a range of attitudes towards road safety were collected using an online survey. A stratified sampling procedure was undertaken to ensure the age, gender and location distributions of participants were representative of the Australian population. A total of 2771 responses were obtained from fully licensed motor vehicle drivers (male: 46%). Confirmatory factor analysis supported the 28-item four-factor DBQ in the Australian sample. The DBQ was also found to be gender-invariant and strong partial measurement invariance was found for drivers aged from 26 to 64, but not for younger (17–25) or older (65–75) drivers. Modifications to the DBQ suggest how the DBQ can be improved for use in these two age groups.